Ocena Systemu motywacyjnego Media Markt - Morys, Dariusz (My University, 2014)
W pracy został poruszony problem motywacji pracowników w organizacji. W pierwszym rozdziale w oparciu o literaturę przedmiotu, poruszono kwestie teoretyczne związane z motywacją pracowników. Ponadto odniesiono się do wczesnych oraz współczesnych teorii związanych z motywowaniem zatrudnionych, które pomagają lepszemu zrozumieniu ich zachowań i oczekiwań. Ich rozmaitość wskazuje, że proces motywowania ulega ciągłym modyfikacją. Następny rozdział koncentruje się na charakterystyce czynników wpływających na satysfakcję pracowników. Omówiono tutaj motywatory płacowe (np. płaca, premia) oraz pozapłacowe (np. szkolenia, świadczenia, komfort psychiczny, możliwość rozwoju), a także omówiono sposób ich oceny. Z kolei rozdział trzeci – praktyczny - dotyczy analizy badanego przedsiębiorstwa Media Markt działającego na terenie Polski. Omówiono historię , profil działalności, misję, cele firmy oraz jej pozycję konkurencyjną, opracowano również analizę SWOT. Na końcu pracy - w ostatnim rozdziale - poddano ocenie system motywacyjny stosowany w Media Markt oraz zaprezentowano własne wnioski z przeprowadzonych badań ankietowych.

This dissertation has considered the problem of motivation among employees in the organization. The first chapter, basing on the literature of the subject, is devoted to theoretical matters connected with the motivation of the employees. Moreover, the references to early and contemporary theories related to the motivation of the employees were made, as they help them to understand certain behaviours and expectations. Their variety indicates that the motivating process is undergoing constant modifications. The second chapter deals with the characteristic of the factors that influence the satisfaction of the employees. Here, the wage motivators (for instance: wages, bonuses) and non-wage were discussed (like: trainings, benefits, psychological comfort or ability to develop), as well the ways of giving the opinions upon them. The last chapter, a practical one, analyses the investigated enterprise, Media Markt, operating throughout Poland. There are some topics that are presented here: the history, undertaking, mission, aims of the company and its competitive position. Also, the SWOT analysis was elaborated. At the end of my dissertation, the motivation system, used in Media Markt, was put under the discussion. Furthermore, my own conclusions from conducting the survey are described in this part.
The assessment of a motivation system in Media Markt
Keywords: motywator; model; teoria motywacji; systemy motywacyjne; materialne i pozamaterialne metody motywacji pracowników; motivator; model; theory of motivation; motivation system; material and non-material methods of motivating employees